2022
DOI: 10.1556/2006.2022.00007
|View full text |Cite
|
Sign up to set email alerts
|

Problematic use of digital media in children and adolescents with a diagnosis of attention-deficit/hyperactivity disorder compared to controls. A meta-analysis

Abstract: Objective Problematic use of digital media and problematic use of the internet (PUI) in particular are growing problems in the general population. Moreover, studies have shown links between PUI and symptoms of attention-deficit/hyperactivity disorder (ADHD). This meta-analysis investigated whether children and adolescents with ADHD are more often affected by PUI compared to control groups. Method Multiple databases (EBSCOhost, Pubmed) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…retrospective clinical case review). Finally, Werling ( 186 ) revealed that youth with ADHD spend more time on digital media and have more severe symptoms of problematic internet.…”
Section: Resultsmentioning
confidence: 99%
“…retrospective clinical case review). Finally, Werling ( 186 ) revealed that youth with ADHD spend more time on digital media and have more severe symptoms of problematic internet.…”
Section: Resultsmentioning
confidence: 99%
“…Reviews have also supported associations between ADHD and sedentary behavior (91)(92)(93)(94)(95) and diet quality (96)(97)(98)(99). Meta-analyses of sedentary behavior found moderate to strong associations between electronic media use and ADHD [(91)…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…The widespread use of screens and mobile devices in the modern world has created a fragmented, rapidly changing digital world where distraction (from the task in hand) is the rule rather than the exception. Children with ADHD may be, especially vulnerable to problematic use (Werling, Kuzhippallil, Emery, Walitza, & Drechsler, 2022). This remains an area in need of more examination for child development in general and for ADHD risk, in particular, whether children with ADHD are more vulnerable to harmful effects (Sonuga‐Barke & Kostyrka‐Allchorne, in press).…”
Section: Environmentsmentioning
confidence: 99%